VALUATION OF SERVICE QUALITY AND INNOVATION OF BOGOR CITY PUBLIC SERVICE MALL - Surawijaya, Angga Alan; Muljono, Pudji; Najib, Mukhamad (Universitas Brawijaya, Indonesia, 2021)
The purpose of this study was to determine the effect of service quality and innovation on visitor satisfaction and loyalty in Bogor City Public Service Mall. Another thing that also needs to be answered from this study is whether there is an effect of customer satisfaction on loyalty in using the services of the Bogor City Public Service Mall. This study used primary data that were collected via interviews and questionnaires distribution to 81 MPP Kota Bogor visitors who were selected by purposive sampling method. The analysis used in this research is modeling analysis using Structural Equation Modeling with the Partial Least Square (PLS) method. The results of this study indicate that service quality has a significant effect on visitor satisfaction and loyalty. Another result is that innovation has a significant effect on visitor satisfaction, but has no significant effect on visitor loyalty. This study also shows that visitor satisfaction has a significant effect on visitor loyalty. Further research is needed with a broader model to explain the diversity of satisfaction and loyalty variables. It is also necessary to conduct a study comparing the services in the Bogor City MPP with the services in the original institution in terms of the level of satisfaction and loyalty of the community.